Acid and Bile Tolerance, Antibacterial Activity, Antibiotic Resistance and Bacteriocins Activity of Probiotic Lactobacillus Species - and S.A. Bhutada, D.H. Tambekar* (Recent Research in Science and Technology, 2010)
Abstract Lactobacilli are an extremely important group of probiotic bacteria inhibit undesirable microflora in the gut and create a healthy equilibrium between beneficial and potentially intestinal pathogens. The study was attempted to isolate Lactobacilli strains from goat milk to search for a new effective antibacterial probiotic strains. FromÂ 40 raw goat milk samples, 48 Lactobacilli isolates were isolated, identified and analyzed for their probiotic properties including acid and bile salt tolerance, antibacterial activity against enteric pathogens, antibiotic resistance patterns and production of bacteriocin. Out of these Lactobacillus species, five isolates were potential probiotics, and bacteriocins produced by them showed demonstrable antibacterial activity against the test pathogens such as S. typhi, Pr. vulgaris, K. pneumoniae, Sh. flexneri, E. aerogenes and E. coli. The bacteriocin produced by L. plantarum (G95a) and L. rhamnosus (G119b) was prominent antibacterial, resistant to heat at 1210C and tolerated acidic pH 3 but sensitive to pH 9. The present study suggested that isolated Lactobacillus strains have an excellent probiotic potential and control of enteric infections and restoration of microbial gut flora. Keywords: Lactobacillus, Acid tolerance, Bile tolerance, Probiotic, Bacteriocin, Antibacterial activity